How communication between nucleosomes enables spreading and epigenetic memory of histone modifications - Erdel, Fabian (Bioessays, 2017)
Nucleosomes “talk” to each other about their modification state to form extended domains of modified histones independently of the underlying DNA sequence. At the same time, DNA elements promote modification of nucleosomes in their vicinity. How do these site-specific and histone-based activities act together to regulate spreading of histone modifications along the genome? How do they enable epigenetic memory to preserve cell identity? Many models for the dynamics of repressive histone modifications emphasize the role of strong positive feedback loops, which reinforce histone modifications by recruiting histone modifiers to preexisting modifications. Recent experiments question that repressive histone modifications are self-sustained independently of their genomic context, thereby indicating that histone-based feedback is relatively weak. In the present review, current models for the dynamics of histone modifications are compared and it is suggested that limitation of histone-based feedback is key to intrinsic confinement of spreading and coexistence of short- and long-term memory at different genomic loci. See also the video abstract here: https://youtu.be/3bxr_xDEZfQ.
Gesehen am 21.11.2018